PENGUATAN NILAI NASIONALISME PADA ANAK USIA DINI MELALUI PENDIDIKAN BAHASA DAN KARAKTER DI ERA GLOBALISASI - Siti Aisyah; Debi Nadziratul Azmi; Edi Susanto; Nur Amirullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of teachers in instilling the values of nationalism in young children through language and character education in the era of globalization. In addition, this research analyzes how the use of the Indonesian language, local culture, and artificial intelligence (AI) technology can support the strengthening of national values among elementary school students. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation involving teachers and learning activities in elementary schools. The findings indicate that teachers play an essential role as role models and facilitators in cultivating nationalism through contextual learning. The Indonesian language serves as the primary medium for fostering love for the homeland, while local culture–based learning effectively enhances students’ pride in regional heritage. The integration of technology and artificial intelligence (AI) also contributes to creating engaging and relevant learning aligned with the demands of modern times.